Biosynthesis of a dual growth factors (GFs) functionalized silk sericin hydrogel to promote chronic wound healing in diabetic mice - Hanxin Deng; Fangyu Wang; Yujuan Zhou; Hexu Lei; Hongji Zhou; Siyu Chen; Zihan Meng; Mengyao He; Ding Tu; He Wang; Xian Li; Qingyou Xia; et al. (Bioactive Materials)
Chronic non-healing wounds, such as diabetic foot, pressure sores and bedsores have seriously affected the life quality of patients worldwide. GFs provide a potential solution to promote chronic wound healing by promoting cell proliferation and differentiation. However, limited resource, high cost, and instability in vivo greatly hindered their clinical applications. In present study, two silk gland bioreactor silkworm stains were generated to successfully synthesize functional silk fibers incorporating high expressions of EGF and PDGF-BB. The two GFs functionalized silk raw materials were used to fabricate a dual GFs sericin hydrogel (E/P-SH) delivering system with tunable material performances for better cell adhesion and biocompatibility, sustainable release of the dual GFs to synergistically promote cell proliferation and migration, which realized the significant healing of chronic full-thickness skin wound in diabetic mice within 12 days with more organized collagen arrangement and better epithelialization degree by reducing inflammatory response and promoting vascularization. These findings demonstrated that the biosynthesized dual GFs-SH delivering system provides an opportunity to broaden the wide utility of GFs in clinical treatment of diabetic wound healing.